Impact of Liver Cirrhosis on Bone Metabolism - Abdalbary, Mohamed; Sobh, Mahmoud; Abdelsalam, Mostafa; Mohamed, Amr El-Husseini (Digestive Disease Interventions, 2022)
Bone loss is an early and major problem in cirrhotic patients. The majority of cirrhotic patients demonstrate evidence of hepatic osteodystrophy (HOD). This includes decreased bone volume, turnover abnormalities, and rarely mineralization defects. Moreover, the degree of bone disease usually correlates with the severity of liver dysfunction. The mechanism of HOD is multifactorial. Vitamin D insufficiency/deficiency, secondary hyperparathyroidism, hypogonadism, inhibitors of bone formation, and mediators/promoters of bone resorption are frequent findings and essential coplayers in HOD. Early and proper identification of HOD is challenging. DXA is the most widely used tool; however, it has fundamental limitations. Bone turnover biomarkers are used to understand the mechanism of bone loss. Bone biopsy with histomorphometry is the gold standard to evaluate bone structure. The evidence for the effectiveness of nonpharmacological and pharmacological management of HOD is limited. Adequate nutrition, weight-bearing exercise, smoking cessation, and limitation of alcohol consumption improve bone health and quality of life. The use of antiresorptive therapies prevents bone loss particularly in patients with high bone turnover. However, osteoanabolics are essential in patients with low bone turnover. Herein, we are discussing the magnitude of the problem, pathogenesis, diagnosis of HOD, and various interventions to improve bone health in cirrhotic patients.
Keywords: liver cirrhosis; bone metabolism; osteoporosis; hepatic osteodystrophy